2007
DOI: 10.1111/j.1526-4637.2007.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameters for the Use of Spinal Cord Stimulation in the Treatment of Chronic Neuropathic Pain

Abstract: Introduction.  Physicians, policy makers, and other interested parties require a synthesized, critical, and clear compilation of the following information to optimize spinal cord stimulation (SCS) for neuropathic pain: 1) indications and potential beneficial outcomes; 2) answers to key clinical questions; 3) cost/resource use implications; and 4) the quality and source of the evidence. This information must be nonjudgmental and noncoercive and have the sole objective of increasing the reader's expertise. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 277 publications
0
121
0
2
Order By: Relevance
“…For instance, the provision of analgesia on demand at any time makes patients feel more in control and less restricted in their daily activities, including return to work. 3 This can lead to improved morale, treatment satisfaction and improvement in depressive symptoms. 3 Studies have also demonstrated that SCS can reduce the requirement for additional pain medications, thereby avoiding the side effects of, and reliance on, pharmacotherapy.…”
Section: Benefits Associated With Spinal Cord Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the provision of analgesia on demand at any time makes patients feel more in control and less restricted in their daily activities, including return to work. 3 This can lead to improved morale, treatment satisfaction and improvement in depressive symptoms. 3 Studies have also demonstrated that SCS can reduce the requirement for additional pain medications, thereby avoiding the side effects of, and reliance on, pharmacotherapy.…”
Section: Benefits Associated With Spinal Cord Stimulationmentioning
confidence: 99%
“…Unlike surgical pain relief procedures, it does not ablate pain pathways or change anatomy. 3 SCS has come a long way in the last 40 years, with more than 14,000 SCS implantations performed worldwide each year for a range of indications. 4 In 1965, Melzac and Wall announced the ''gate theory'', proposing that activating large, myelinated afferent nerve fibers would inhibit transmission in small, unmyelinated primary afferent nerves in the dorsal horn of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Often times, the psychiatrist/psychologist will have only one encounter with the patient, compared to the longitudinal relationship developed between the patient and pain practitioner. Indeed, a 40-year literature review by North and Shipley assessing "psychological predictors" concluded, "We lack sufficient information to predict SCS outcome from the result of a pretreatment psychological evaluation, but SCS, as is the case for every interventional pain treatment, is reserved for patients with no evident unresolved major psychiatric co-morbidity" [26].…”
Section: Patient Selectionmentioning
confidence: 99%
“…[19][20] Whereas the power to detect clinically meaningful differences in ischemic pain trials is still quite inadequate. [13,[21][22][23][24][25] In recent years, research into the therapeutic effect of SCS in control of ischemic pain secondary to peripheral vascular disease particularly in inoperable CLI has become a hot topic around the world. For more than ten million patients, it would be good news if the curative effect of SCS on CLI has been confi rmed clinically.…”
Section: History Of Scsmentioning
confidence: 99%